The Microbiome and Irritable Bowel Syndrome – A Review on the Pathophysiology, Current Research and Future Therapy - Chong, Pei Pei; Chin, Voon Kin; Looi, Chung Yeng; Wong, Won Fen; Madhavan, Priya; Yong, Voon Chen (Frontiers in Microbiology, 2019)
Irritable bowel syndrome (IBS) is a functional disorder which affects a large proportion of the population globally. The precise etiology of IBS is still unknown, although consensus understanding proposes IBS to be of multifactorial origin with yet undefined subtypes. Genetic and epigenetic factors, stress-related nervous and endocrine systems, immune dysregulation and the brain-gut axis seem to be contributing factors that predispose individuals to IBS. In addition to food hypersensitivity, toxins and adverse life events, chronic infections and imbalance in the gut microbiota have been suggested to trigger IBS symptoms in tandem with the predisposing factors. This review will summarize the pathophysiology of IBS and the gut microbiome in relation to IBS. Current methodologies for microbiome studies in IBS such as genome sequencing, metagenomics, culturomics and animal models will be discussed. The myriad of therapy options such as immunoglobulins (immune-based therapy), probiotics and prebiotics, dietary modifications including FODMAP restriction diet and gluten-free diet, as well as fecal transplantation will be reviewed. Finally this review will highlight future directions in IBS therapy research including identification of new molecular targets, application of 3-D gut model, gut-on-a-chip and personalized therapy.